Relevansi Nilai Tasawuf Sosial di Era Globalisasi Menurut Habib Husein Jafar - Anwar, Khoirul (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
Human life in the era of globalization has become easier and faster. However, this convenience comes with negative impacts, leading to increased individualism, excessive consumption, wastefulness, and the rapid spread of hate speech. To address the complex effects of globalization, social Sufi values are applied by figures such as Habib Husein Jafar Al-Hadar. Habib Husein Jafar, an Islamic scholaractively involved in social media-based preaching, consistently applies a Sufi approach in every aspect of his preaching. This research employs a qualitative research approach using a figure's thought study with a literature review, utilizing content analysis techniques. Data collection involves digital and print documentation related to the theme of social Sufism, with digital documentation from the Jeda Nulis channel and the LogIn program, and printed documentation from books authored by Habib Ja’far. The findings emphasize the significance of applying social Sufi values in this era to cultivate individuals who are pious both ritually and socially. Three social Sufi values identified in Husein Ja’far Al-Hadar's thinking include a minimalist lifestyle, a moderate attitude, and practicing good relations(silaturahmi). Minimalist values teach simplicity, avoidance of the forbidden, and acceptance within one's capacity. Moderate attitude and practicing good relations (silaturahmi) create a life that ensures happiness not only in this world but also in the hereafter, fostering harmonious relationships and preventing individualistic, egoistic, and antagonistic behaviors.